7.379 % Power Conversion Efficiency of a Numerically Simulated Solid-State Dye-Sensitized Solar Cell with Copper (I) Thiocyanate as a Hole Conductor - Danladi, Eli; Kashif, Muhammad; Daniel, Thomas; Achem, Christopher; Alpha, Matthew; Gyan, Michael (East European journal of physics, 2022)
Sourcing for an alternative to the liquid electrolyte in dye-sensitized solar cells (DSSCs) have been the subject of interest in the photovoltaic horizon. Herein, we reported by means of simulation, the performance of dye-sensitized solar cell by replacing the liquid electrolyte with a copper (I) thiocyanate (CuSCN) hole conductor. The study was carried out using Solar Capacitance Simulation Software (SCAPS) which is based on poisson and continuity equations. The simulation was done based on an n-i-p proposed architecture of FTO/TiO2/N719/CuSCN/Pt. The result of the initial device gave a Power Conversion Efficiency (PCE), Fill Factor (FF), Short Circuit Current Density (Jsc) and Open Circuit Voltage (Voc) of 5.71 %, 78.32 %, 6.23 mAcm-2, and 1.17 V. After optimizing input parameters to obtain 1×109 cm-2 for CuSCN/N719 interface defect density, 280 K for temperature, 1.0 μm for N719 dye thickness, 0.4 μm for TiO2 thickness, Pt for metal back contact, and 0.2 μm for CuSCN thickness, the overall device performance of 7.379 % for PCE, 77.983 % for FF, 7.185 mAcm-2 for Jsc and 1.317 V for Voc were obtained. When compared with the initial device, the optimized results showed an enhanced performance of ~ 1.29 times, 1.15 times, and 1.13 times in PCE, Jsc, and Voc over the initial device. The results obtained are encouraging and the findings will serve as a baseline to researchers involved in the fabrication of novel high-performance solid-state DSSCs to realize its appealing nature for industry scalability.